Dual Arterial Access for Stenting of Aortic Coarctation in Patients with Near-Total Descending Aortic Interruption. Issue 2 (December 2015) - Hamid, Tahir; Jamallulail, Syed; Clarke, Bernard; Mahadevan, Vaikom
Abstract Endovascular stenting is a recognized treatment strategy for the treatment of coarctation of aorta (COA) in adults. The aortic coarctation is usually crossed retrogradely from the descending aorta via the femoral approach. We report three patients who had near-total descending aortic interruption and underwent successful stenting of severe COA using a combined radial/brachial and femoral approach due to difficulty in crossing the lesion retrogradely via a femoral approach. There were no procedural complications and no adverse events during 6 months of follow-up.